Diagnostic Studies and Structural Analysis during the Restoration of St. Sophia Cathedral - Afat, Mammadova; Ibrahimli, Habib (Azerbaijan Science Center, 2025)
The historical architectural masterpiece Hagia Sophia stands in Istanbul, Turkey, as one of the most impressive structures ever built. The cathedral suffered multiple earthquakes and fires throughout fifteen centuries, which caused partial building collapses that required extensive reconstruction work. The current state of the building structure needs detailed knowledge about its actual condition for proper modern conservation work. The research combines various diagnostic methods, which include geometrical survey and crack mapping, and non-destructive testing with ground-penetrating radar, ultrasonic testing, and thermography, and structural monitoring, and laboratory material analysis to determine Hagia Sophia's present condition for developing a complete conservation plan. The dome shows ongoing vertical and ring-shaped cracks, while the supporting columns show signs of uneven weight distribution, and the building materials match those used during the Byzantine era. The building shows stability, but it faces risks from earthquakes and ongoing decay. The proposed conservation plan includes protective measures and scheduled maintenance checks and ongoing surveillance to protect this cultural treasure for future generations.